Pengungkapan Informasi Lingkungan oleh Perusahaan di Indonesia - Devian Siti Aminah; Suwarno Suwarno (Prodi Akuntansi - FEB Universitas Muhammadiyah Gresik, 2019)
The purpose of this study is to analyze the factors that influence disclosure of environmental aspects information in manufacturing companies. These factors are firm age, public share ownership, profitability, leverage, and industry type. The population of this research are companies listed on the IDX 2016-2018. The samples of this study are 130 manufacturing companies using a purposive sampling method. This research uses multiple regression methods to test the hypothesis. The Environmental disclosure score index used is the Indonesian Environmental Reporting Index (IER). The result of this study shows as industry type has a significant positive influence on environmental aspects information but firm age, public share ownership, profitability, and leverage did not have a significant influence on environmental aspects information in companies.